Analisis IT Service Management Menggunakan Framework ITIL V4 pada RSUP Dr. Mohammad Hoesin Kota Palembang - Dedi Ferdinan Manalu; Dicky Pratama (STMIK Banjarbaru, 2026)
Information Technology Service Management plays a crucial role in supporting effective and sustainable hospital operations. Dr. Mohammad Hoesin General Hospital, Palembang City, still faces several IT service challenges, such as system and network disruptions, and suboptimal service management. This study aims to analyze the maturity level of IT services using the ITIL V4 Framework in Incident Management, Problem Management, and Service Continuity Management practices. The study used a mixed methods approach with observation, interviews, literature studies, and questionnaires. The results showed that the maturity level of Incident Management practices was 4.1, Problem Management was 4.04, and Service Continuity Management was 3.94, which are at Level 4 (Managed). This study resulted in recommendations for the development of IT service SOPs, improved system monitoring, and strengthened documentation and backup recovery processes.Keywords: IT Service Management; ITIL V4; Incident Management; Problem Management; Service Continuity Management. AbstrakPengelolaan layanan teknologi informasi memiliki peranan penting dalam mendukung operasional rumah sakit agar berjalan efektif dan berkelanjutan. RSUP Dr. Mohammad Hoesin Kota Palembang masih menghadapi beberapa kendala layanan TI seperti gangguan sistem, jaringan, dan pengelolaan layanan yang belum optimal. Penelitian ini bertujuan untuk menganalisis tingkat kematangan layanan TI menggunakan Framework ITIL V4 pada praktik Incident Management, Problem Management, dan Service Continuity Management. Penelitian menggunakan pendekatan mixed methods dengan teknik observasi, wawancara, studi literatur, dan kuesioner. Hasil penelitian menunjukkan nilai maturity level pada praktik Incident Management sebesar 4,1, Problem Management sebesar 4,04, dan Service Continuity Management sebesar 3,94 yang berada pada Level 4 (Managed). Penelitian ini menghasilkan rekomendasi berupa penyusunan SOP layanan TI, peningkatan monitoring sistem, serta penguatan dokumentasi dan proses backup recovery.